Pest and Disease Identification in Parijoto Plant (Medinilla speciosa blume) at Nglurah Tawangmangu - Weli Umiyati; Manda Ayu Pramesti; Elin Pujiastutik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Parijoto (Medinilla speciosa blume) is a tropical plant that has purplish pink fruit often called Asian grape. In Indonesia, parijoto plants are very well known as ornamental plants that have various benefits, from parijoto fruit can be used as anti-inflammatory drugs so that ornamental plants are widely cultivated by the community, especially lovers of ornamental plants and ornamental plant cultivation in Nglurah. Medinilla speciosa blume is very suitable in Indonesia, which has a tropical climate, but the high rainfall in Indonesia in the rainy season should get more attention in caring for it. This makes parijoto plants susceptible to several types of diseases and pests that can damage the beauty of the Medinilla speciosa blume plant. However, the lack of experts in this field makes it very difficult for plant lovers and the cultivation community of Medinilla speciosa blume in Nglurah to solve the problem of diseases and pests that attack the Medinilla speciosa blume plant. The purpose of this study was to determine pests and diseases on Medinilla speciosa blume. This research was conducted in Nglurah Village Rt 01 Rw 02 Tawangmangu for five days on 04 Ã¢â¬â 08 September 2021. This research uses observation and interview methods. Data were analyzed by qualitative descriptive. This study used 10 samples of the observed Medinilla speciosa blume plant. The tools used are cellphone cameras and stationery. The variables to be observed are pests and diseases. The results of this study found 4 pests and 2 diseases on Medinilla speciosa blume including Fussarium oxysporum, Cercospora sp and Pestalotia sp, mealybugs, caterpillars, snails, grasshoppers. For this reason, the solution for treating parijoto plants to avoid pests and diseases requires extra care such as paying attention to soil moisture, giving appropriate fertilizers, and giving vitamins so that parijoto plants can grow well.